Maternal factors associated with low birth weight infants - Choironi, Emi Azmi; Pratama, Yanasta Yudo; Asya, Kahaya Ainin; Adnan, Muhammad Luthfi; Kuntari, Titik; AbuHilail, Hamza Sameeh Abd El Qader (JHeS (Journal of Health Studies), 2025)
Indonesia has the second-highest prevalence of low birth weight (LBW) babies in ASEAN countries. Various factors contribute to this high incidence. This study examined the association between gestational weight gain (GWG), pre-pregnancy body mass index (BMI), and antenatal care (ANC) visits frequency towards LBW in a region of Indonesia with a high prevalence of LBW. This is an analytical observational study using cross-sectional design with utilizing medical records data, conducted in June-August 2022. We analyzed 78 medical records of pregnant women who gave term-singleton birth. Main independent variables were gestational weight gain, pre-pregnancy BMI, and ANC frequency. Data analysis was performed using statistical package program, including descriptive statistics, bivariate and multivariate analyses to explore associations between those factors and LBW occurrence. The mean of infant birth weight was 3115.4± 465.2 grams. Low birth weight proportion was 11.5%. More than 90% of subjects follow frequency of ANC visits for K1 and K4, but only a third of participants meet K6 ANC visit recommendation. Approximately half of the subjects (48.7%) had inadequate GWG. Bivariate analysis revealed a strong association between insufficient GWG and LBW (OR = 10.4, 95% CI = 1.233–87.74, p=0.013). However, pre-pregnancy BMI and ANC frequency showed no association with LBW. Inadequate gestational weight gain is significantly linked to an elevated risk of LBW. Emphasizing the appropriate quantity of ANC visits and regular monitoring of maternal weight gain throughout pregnancy is crucial to mitigate the risk of LBW.